The Nuclear Disarmament Cases: Is Formalistic Rigour in Establishing Jurisdiction Impeding Access to Justice? - Ramkumar, Meenakshi; Singh, Aishwarya (Utrecht Journal of International and European Law, 2017)
Nuclear disarmament falls within the purview of the purposes envisaged in Article 1 of the United Nations Charter. The International Court of Justice (ICJ) in 1996 delivered an advisory opinion on legality of use of nuclear weapons and has stated that the states in good faith must strive towards nuclear disarmament. In the Marshall Islands Cases, 20 years later the ICJ had the opportunity to address questions relating to cessation of the nuclear arms race and nuclear disarmament. However, the ICJ has failed to foster nuclear disarmament within the international community. The ICJ dismissed Marshall Islands’ application on jurisdictional grounds because there was no legal dispute between the parties. The ICJ in determining the existence of a dispute introduced a subjective awareness test. In this case note, we aim to examine the awareness test and its politico-legal effects in the development of international law. While doing so, we also argue that the test has further rendered the enforcement of nuclear disarmament obligations arduous.